1994
DOI: 10.1002/anie.199409691
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of the First Dimeric Iminoalane Containing an Al2N2 Heterocycle

Abstract: An almost ideal planar Al2N2 ring as a central unit and the lowest degree of oligomerization for the class of compounds is shown by the dimeric iminoalane 1, which is formed from (Cp*Al)4 and Me3SiN3. The fact that no heterocubane results is attributed to the steric demand of the Cp* and SiMe3 groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 24 publications
1
55
0
2
Order By: Relevance
“…This increases the likelihood of association. On the other hand, the reaction between a univalent metal species and an organoazide [7,11] (e.g., [Eq. (1)]) increases the metal coordination number, and leaves that of nitrogen unchanged, with the result that steric crowding becomes greater.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This increases the likelihood of association. On the other hand, the reaction between a univalent metal species and an organoazide [7,11] (e.g., [Eq. (1)]) increases the metal coordination number, and leaves that of nitrogen unchanged, with the result that steric crowding becomes greater.…”
mentioning
confidence: 99%
“…(1)]) increases the metal coordination number, and leaves that of nitrogen unchanged, with the result that steric crowding becomes greater. Nonetheless, previous reactions of this type involving [Cp*M] (Cp* h 5 -C 5 Me 5 , M Al or Ga) with the azides RN 3 (R Si(iPr 3 ) 3 , Si(tBu) 3 , SiPh 3 , or 2,6-Me 2 C 6 H 3 ) have generally led to dimers [(Cp*MNR) 2 ], [7,11] which suggested that the substituents were insufficiently large to prevent association. In contrast, the recently synthesized metal(i) species [{HC(CMeDippN) 2 }M : ] [12,13] and the bulky azide N 3 -2,6-Trip 2 C 6 H 3 [14] provide the exceptional degree of crowding required to stabilize monomeric species, thereby enabling the isolation of the imides 1 and 2.…”
mentioning
confidence: 99%
“…5 . [19] With R = 2,4,6-(tBu) 3 C 6 H 2 and R' = C 6 H 5 , one obtains values of 182.4 pm and 88.88 for the AlÀN bond distance and the NÀAlÀN bond angle, respectively.…”
Section: Alnhmentioning
confidence: 96%
“…Current research continues to uncover fascinating new ring systems which pose intriguing questions with respect to their bonding or which exhibit unexpected reactivity. Some noteworthy examples include 6p-electron gallium-based systems and pseudo aromatic cyclic silylenes [1,2], novel cyclic tellurium imides [3] and interesting aluminum-nitrogen heterocycles [4] among others [5][6][7][8]. In addition to the studies on bonding and reactivity, a further reason for studying inorganic rings is their potential use as precursors to polymers and solid-state materials.…”
Section: Introductionmentioning
confidence: 98%